An Analysis Of Electrical Energy Usage In Alternating Current (AC) Motors 1 Phase Using Inverter - Sigit Pratama; Solly Aryza; Haris Gunawan (Sean Institute, 2024)
1 Phase AC motors are often used as drivers on equipment with full speed or relatively constant speed, especially in industry or households. Power consumption on 1 Phase AC motors with constant speed is greater, therefore it can cause waste in the use of electrical energy. To overcome this problem, a way is needed to save electrical energy, especially in the operation of 1 Phase AC motors. One effort to save on electrical energy consumption, especially in the use or operation of 1 Phase AC motors is by using a power converter in the form of an inverter. From the results of the study that has been obtained, the use of 1 Phase AC Motors when operated using two motors without being connected to an inverter, the power measured on the measuring instrument reaches 0.796 kW with electrical energy of 1.194 kWh. If the 1 Phase AC Motor is operated using an Inverter, the power measured on the measuring instrument reaches 0.408 kW with electrical energy of 0.612 kWh. The comparison of the use of electrical energy of 1 Phase AC motors using an inverter is lower than the use of electrical energy of 1 Phase AC motors without using an inverter, which can be used as savings in electrical energy in monthly usage.